Challenging Anti-Black Racism in Everyday Teaching, Learning, and Leading: From Theory to Practice. Issue 1 (January 2021) - Lopez, Ann E.; Jean-Marie, Gaëtane
Anti-Black racism and White supremacy continue to have dire impact on the lives and educational outcomes of Black people and students in educational spaces. Examining ways in which this form of racism is disrupted, confronted, and challenged in education and schooling is important not only to Black students, scholars, practitioners, and staff, but to all People of Color. Drawing on research conducted with educators in, Canada, the United States and our lived experiences as Black educators this article examines how antiblackness and anti-Black racism is manifested in schooling spaces through teaching, learning, and leadership, and offers actions that educators can take in everyday practice to confront and disrupt. In so doing connect theory to practice, and offer possibilities that school leaders and others can act on.